Espetáculo midiático como manipulação das massas na adaptação cinematográfica Jogos vorazes: em chamas - Passaura, Luana (2025)
This study aims to analyze how the media spectacle occurs as a form of mass manipulation in the film adaptation of The Hunger Games: Catching Fire. To this end, it is important to note that the contemporary era opens space for new dialogues between the arts, so that while classical European literature was previously considered the most important art, over time, the possibility of understanding and analyzing other ways of telling a story has become visible. In order to construct the research, it is important to create a space for discussion on questions of intermedialities, film adaptation, and the construction of the film image, through cinema and literature. Thus, the authors who will constitute the work will be the studies of Clüver (1997, 2006), Rajewsky (2012) and Müller (2012), which provide an understanding of intermedialities; the construction of intertextuality by Genette (2005) and Stam (2006); consecutively, questions about fidelity and cinematographic adaptation, which will be discussed through Stam (2006) and Hutcheon (2013). The methodology used is through the bibliographical readings presented, which help in the objective of the research, which is precisely to understand this construction of the manipulation of the masses within the work, through the constructed media. In this way, the study presents this bridge between literature and cinema that provides an opportunity to look at the contemporary, in which the reader and viewer can immerse themselves within a narrative creation. It is clear, therefore, that the construction of the research provides an opportunity to understand media manipulation, based on the construction of the society of Panem, as well as the technological and dystopian issues that are key points for the narrative.